Manejo agronomico del cultivo de cafe (Coffea arabica L.) en etapa de vivero, variedad Parainema, San Juan del Rio Coco, Madriz, Nicaragua, 2019 - Villarreyna Alvarado, Elder Alfredo (2020)
Sumarios (Es, En)